2024
DOI: 10.1186/s13046-023-02910-y
|View full text |Cite
|
Sign up to set email alerts
|

A novel PDPN antagonist peptide CY12-RP2 inhibits melanoma growth via Wnt/β-catenin and modulates the immune cells

Chunyan Feng,
Albert Yu,
Zhongfu Wang
et al.

Abstract: Background Podoplanin (PDPN) is a highly conserved, mucin-type protein specific to the lymphatic system. Overexpression of PDPN is associated with the progression of various solid tumors, and plays an important roles in the tumor microenvironment by regulating the immune system. However, the role of PDPN-mediated signal activation in the progression of melanoma is still unknown. Methods PDPN expression was first analyzed in 112 human melanoma tissu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Besides on FLS, PDPN is expressed in many tumors and normal cells, especially lymphatic epithelial cells and follicular DCs [ 60 ]. PDPN has been studied in cancer as a therapeutic target by using antibodies or antagonistic peptides [ 61 , 62 ]. In RA, Christopher D Buckley et al reported in 2018 that anti-PDPN antibodies efficiently protected mice with CIA from arthritis [ 63 ].…”
Section: Strategies For Targeting Pathogenic Fls Subsets In Ramentioning
confidence: 99%
“…Besides on FLS, PDPN is expressed in many tumors and normal cells, especially lymphatic epithelial cells and follicular DCs [ 60 ]. PDPN has been studied in cancer as a therapeutic target by using antibodies or antagonistic peptides [ 61 , 62 ]. In RA, Christopher D Buckley et al reported in 2018 that anti-PDPN antibodies efficiently protected mice with CIA from arthritis [ 63 ].…”
Section: Strategies For Targeting Pathogenic Fls Subsets In Ramentioning
confidence: 99%
“…1,2 As the treatment of melanoma tumors remains challenging in clinics due to elevated rates of drug resistance and rapid metastasis formation, there is a need for the development of new therapeutic mechanisms and anticancer strategies. 1,3 Metabolic adaptability plays a crucial role in the proliferation and viability of cancer cells and represents a significant factor in the efficacy of anticancer treatments. 4–6 During tumor genesis and development processes, cancer cells strategically choose metabolic alterations that optimize the tumor microenvironment, thereby promoting cancer cell survival and proliferation.…”
Section: Introductionmentioning
confidence: 99%